Transport of an electron wave packet through a nanostructure in a magnetic field - Gunnar Þorgilsson 1982- (2007)
A model is developed for a time dependent transport of a wave packet through a quantum wire with an embedded nanostructure in a perpendicular homogeneous magnetic field. The model is built on the Lippmann-Schwinger formalism of scattering theory in coordinate-momentum space as introduced by Gurvitz [1]. Four different nanostructures are studied by using the model: a constriction, a quantum ring, a donor-like impurity and an acceptor-like impurity. In the results from the simulations we observe phenomena such as skipping orbits, self-interference, and mode mixing, effects which have all been seen in the static case [1-5]. In addition we observe time lags and transition to short or long lived intermediate states, effects that are not directly observable in the static case. [1] S. A. Gurvitz, Phys. Rev. B 51, 7123 (1995). [2] J. H. Bardarson, Master's thesis, University of Iceland, RH-09-2004.html, 2004. [3] J. H. Bardarson et al., Phys. Rev. B 70, 245308 (2004). [4] V. Gudmundsson et al., Phys. Rev. B 71, 235302 (2005). [5] G. Cattapan and E. Maglione, Am. J. Phys. 71, 903 (2003). Þróað er líkan fyrir tímaháðan flutning rafeinda bylgjupakka í gegnum skammtavír með ígræddum nanóstrúktúr í þverstæðu einsleitu segulsviði. Líkanið er byggt á Lippmann-Schwinger framsetningu dreififræði í raun- og skriðþungarúmi sem Gurvitz kynnti [1]. Skoðaðir eru fjórir mismunandi nanóstrúktúrar með líkaninu: hindrun, skammtahringur, rafgjafi og rafþegi. Í niðurstöðum líkansins sjáum við fyrirbæri líkt og skoppbrautir, sjálfvíxl og blöndun orkuorða, sem öll hafa fundist í æstæða tilvikinu [1-5]. Að auki sjáum við tímaseinkun og ástandsbreytingu í skamm- og langlíf milliástönd, fyrirbæri sem eru ekki sjáanleg í æstæða tilvikinu. [1] S. A. Gurvitz, Phys. Rev. B 51, 7123 (1995). [2] J. H. Bardarson, Master's thesis, University of Iceland, RH-09-2004.html, 2004. [3] J. H. Bardarson et al., Phys. Rev. B 70, 245308 (2004). [4] V. Gudmundsson et al., Phys. Rev. B 71, 235302 (2005). [5] G. Cattapan and E. Maglione, Am. J. Phys. 71, 903 ...